Characterization of Bioplastic from Cassava Peel Using Fourier Transform Infrared (FTIR) Spectroscopy - Fong Chui Nee; Siti Amira Othman; Nur Amirah Elias; Siti Nursyakirah Idris; Nur ‘Izqa Ashiqin Mohd Najib (Multidisciplinary Applied Research and Innovation, 2023)
The importance of this research project is to gain knowledge in every process including preparation and characterization of irradiated bioplastic by making good use of the agriculture waste product. Since the Earth has this concerning issue of solid waste pollution caused by an abundance of thrown plastics, biodegradable plastics will become the main substitution for the usage of plastics. Since the bioplastic is produced from the agricultural waste product which can be decomposed, it is a more environmentally friendly material to replace plastics in our daily lives. Besides, bioplastics will make a significant contribution in making our planet earth a better place. Since they are generated from natural renewable resources and biodegradable, they can assist in diminishing dependency on fossil fuels, boosting sustainability programs, and allowing manufacturing to diversify feedstocks.